Study of the relationship between anxiety level and coping strategies among students - Kapbasova, G.B.; Кapasheva, G.А.; Algozhina, A.R. (Ye.A.Buketov Karaganda State University Publ., 2019)
Modern social psychology is increasingly paying attention to behavioral strategies in conflict, stressful, anxious situations. First of all, it is due to the fact that the person is inextricably linked with social conditions; almost all face crisis situations and develop a specific strategy to overcome it. Interest in such strategies appeared relatively recently. Therefore, one of the most important problems that a modern student has to solve is the development of an adequate coping behavior to level the level of anxiety. To identify the relationship between the level of anxiety and coping strategy, a study was conducted among 2nd year students, in the amount of 31 people, in the specialty psychology of Karaganda State Unversity named after Ye.A. Buketov. The average age of the subjects from 19 to 20 years. The article analyzes the concept of anxiety, situational anxiety and personal anxiety; conditions and signs of anxiety development in students; factors affecting the development of anxiety. Analysis of the research results shows that students with different levels of anxiety have different types of coping strategies. Respondents who showed a low level of personal anxiety chose «distancing» and «positive reappraisal» coping, respondents who showed an average level chose «distancing », «positive reappraisal», «escape-avoidance», «acceptance of responsibility» and «problem solving planning » coping, and those who showed a high level chose escape-avoidance coping. The results of the study can help identify problem areas in the organization of psychological assistance to students.
Студенттердің үрей деңгейі мен копинг-стратегияларының өзара байланысын зерттеу
Исследование взаимосвязи уровня тревожности и копинг-стратегии у студентов
Keywords: students; anxiety; coping strategies; personal anxiety; situational anxiety; types of coping startups; stress